2009 International Conference on Computer Engineering &Amp; Systems 2009
DOI: 10.1109/icces.2009.5383285
|View full text |Cite
|
Sign up to set email alerts
|

DCT assisted speaker identification in the presence of noise and channel degradation

Abstract: This paper presents a robust speaker identification method from degraded speech signals. This proposed method depends on the Mel-frequency cepstral coefficients (MFCCs) for feature extraction from the degraded speech and its discrete cosine transform (DCT). It is known that the MFCCs based speech recognition methods are not robust enough in the presence of noise and channel degradation. So, the feature extraction from the DCT of the signal will assist in achieving a higher recognition rate. The artificial neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Recently, a lot of research works adopted DTs such as DWT [5], DCT [8], and DST [9] for feature extraction. These DTs have an excellent energy compaction property, which is suitable for the elimination of the noise effect.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a lot of research works adopted DTs such as DWT [5], DCT [8], and DST [9] for feature extraction. These DTs have an excellent energy compaction property, which is suitable for the elimination of the noise effect.…”
Section: Figurementioning
confidence: 99%
“…These DTs have an excellent energy compaction property, which is suitable for the elimination of the noise effect. Shafik et al [8] proved that the identification of speakers with features extracted from DTs, such as DWT and DCT, gives better recognition rates. Li et al [9] suggested the utilization of the DST in the speaker identification systems.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The drawback of the MFCCs is the poor performance with noise. Recently, a lot of research adopted discrete transforms such as DWT [37], DCT [36], and DST [24] for feature extraction. These discrete transforms have an excellent energy compaction property, which is suitable for the elimination of the noise effect.…”
Section: Introductionmentioning
confidence: 99%
“…These discrete transforms have an excellent energy compaction property, which is suitable for the elimination of the noise effect. Shafik et al [36] and Abd El-Samie et al [3] proved that the identification of speakers with features extracted in transform domains such as DWT, DCT gives better recognition rates. Li et al [24] proposed the utilization of the DST in the speaker identification systems.…”
Section: Introductionmentioning
confidence: 99%